Exploring the Role of Code-Switching in Multilingual Classroom Dynamics: A Comparative Study of Attitudes and Practices among University Students in the Philippines - Maranan, Mario; Batalla, Regina; Santos, Arren (JPAIR Multidisciplinary Research, 2025)
This study investigates the usage and attitudes towards code-switching among university students in the Philippines, focusing on its role in promoting inclusive and equitable education. The research addresses the gap in understanding the implications of code-switching in educational settings, particularly in a multilingual context where native languages and English are used in instruction. A descriptive correlational research design was employed, utilizing an online questionnaire to collect data from a random sample of 205 students across three universities. The survey measured the frequency of intersentential, intrasentential, tag, situational, and metaphorical code-switching and attitudes toward these practices. Pearson's R correlation coefficient was used to analyze the relationship between respondents' profile variables and their perceptions and usage of code-switching. The significant findings reveal that while code-switching is not frequently practiced, with a weighted mean of 2.341 indicating its rarity, it is nonetheless viewed positively, with a weighted mean of 3.141 reflecting an "Acceptable" attitude towards its use in the classroom. Situational code-switching emerged as the most common type, with a total weighted mean of 3.116, indicating general agreement with its use. The study concludes that code-switching is a valuable communicative strategy, potentially aiding in more inclusive and equitable education. The study recommends further research to explore the reasons behind the low frequency of code-switching usage and to identify barriers that may prevent its more widespread adoption. Additionally, professional development for teachers on effective code-switching strategies and the consideration of positive attitudes towards code-switching in educational policy development are suggested.
Keywords: Code-Switching; Multilingual Education; Classroom Communication; Inclusive Education; Language Attitudes; descriptive correlational design; Philippines